Accessibility and Participation: South Sumatra KPU Efforts to Present Disability-Friendly Elections in the city of Palembang in 2024 - Amaliatulwalidain; Peni Masito; Dwiki Adi Putra (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to identify the strategy of the South Sumatra Provincial KPU in increasing the participation of voters with disabilities in the 2024 Presidential election in Palembang City, as well as the obstacles and factors that affect the effectiveness of the strategy. The research method used is a descriptive qualitative approach, by collecting data through observation, interviews, and documentation at the South Sumatra Provincial KPU office, as well as the chairman of KPPS, and the Disability Group. Data analysis is carried out through data collection, data reduction, data presentation as well as verification and affirmation of thematic conclusions based on Strategy Theory (Mulgan, 2009:19) and Political Participation Theory (Budiardjo, 2019), to identify the KPU strategy as well as the obstacles and factors that affect the effectiveness of the strategy. The results of the research revealed that the South Sumatra Provincial KPU implemented various strategies to increase the participation of voters with disabilities in the 2024 Presidential Election. The strategy includes direct socialization to communities and social institutions, the use of social media and tools such as braille, and training for KPPS to be able to provide inclusive services. The KPU also involves people with disabilities in election simulations and public service advertisements to increase their political awareness. Facilities at the polling station are prepared to be disability-friendly, such as special lanes, wheelchairs, and pick-up services. Cooperation with social institutions and communities with disabilities also strengthens the dissemination of information. Despite obstacles such as limitations of disability-friendly information media and psychological barriers, this strategy is considered effective in increasing the confidence and political participation of people with disabilities. This effort reflects the commitment of the South Sumatra KPU in realizing inclusive, fair, and equal elections for all. Based on the results of the research, the South Sumatra Provincial KPU's strategy in increasing the participation of voters with disabilities in the 2024 Presidential Election in Palembang City shows a positive commitment, but still faces obstacles. The goal of political inclusion has been well directed, but the provision of facilities and information still does not fully support the needs of people with disabilities, especially for sensory and intellectual disabilities. Socialization is not yet fully accessible, and the involvement of people with disabilities in decision-making is still limited. The participation rate is still mostly passive due to lack of information, physical barriers, and psychological and social factors. To realize inclusive elections, the KPU's strategy needs to be strengthened through increased accessibility, involvement of the disability community, and more disability-friendly communication methods.